Health Management Workforce for India in 2030 - Ritika Tiwari; Himanshu Negandhi; Sanjay P. Zodpey (Frontiers Media S.A., 2018)
Introduction: Since its launch in the year 2005, National Rural Health Mission (NHM) has exhibited a felt need for health management training in India against the background of a shortfall of trained public health managers in the country. In India's context, health (hospital) management professionals are those, who are working in the health sector, belonging to medical and non-medical backgrounds and are trained in health (hospital) management/administration programs or other public health programs (for e.g., Master of Public Health) wherein health (hospital) management/administration is significant part of the curriculum. The presence of trained management professionals in the health sector has grown over the years.Objectives: To estimate the supply, need and requirement for health management professionals for India in the year 2030.Materials and methods: The supply data for health management professionals was calculated based on the output from various academic programs related to health management/administration and other public health programs. Need was calculated using "service target approach" and benchmark analysis with 2.97 health managers per 100,000 population (NACCHO 2011). Supply-need gap was estimated using normative need as base number for projections whereas for rest of the years (2018-2030) projections were done at a constant growth rate as per India's population projections.Results: The overall supply capacity of trained health management professionals was 3,463 for 2017. However, based upon a service target approach India requires 11,304 health management professionals in 2017. If India is to reach the normative standards of 2.97 health managers per 100,000 population, the country would need 39,774 health management professionals in 2017. This need would increase to approximately 44,936 health management professionals by the year 2030 to maintain the normative standard of 2.97 health managers per 100,000 population.Conclusions: The supply side will match the requirement of HMPs earliest by the year 2026 in a high seat occupancy scenario.Moreover, there is a need to improve the quality of the output in terms of an explicitly stated and standardized competency framework that is tailored to the Indian context.